Using Artificial Neural Network Model to Forecast the Electricity Consumption in Algeria - SARI-HASSOUN , Salaheddine; NAMANE , Mohamed Abdeldjalil; MALIOUI , Abdelghani (Dirassat Journal Economic Issue, 2024)
Recent events, especially the Russian-Ukrainian War have demonstrated the significance of energy resource, which is generally regarded as one of the most fundamental components of global economies and is classified as a strategic component of economic development. In this study, we employed the artificial neural networks to predict the electricity consumption of Algeria using annual data 1980 to 2022. After discussing this method’s methodology and the diagnostic phase, the model’s Multi-Layer Perceptron neural networks (MLP) were chosen. MLP 3-1-1 was found to be the most effective model. In the forecasting phase, the electricity consumption energy in Algeria was predicted to be 76,83 billion TWh in 2023 and 79,47 billion TWh in 2024, an increase of 3,434%.